Efficacy and safety of sodium stibogluconate compared to meglumine antimoniate in the treatment of cutaneous leishmaniasis in Peru - Llanos-Cuentas, Alejandro (2023)
Objective:To compare the efficacy and safety of sodium stibogluconate (SS) and meglumine antimoniate (MA) in the treatment of cutaneous leishmaniasis (CL) in a general hospital.Methods: Case-series of 193 patients with CL treated in three clinical trials with MA (n=69) and SS (n=124) during 2001-2010. Both study drugs were administered intravenously at a slow speed at 20 mg Sb5+/kg/day for 20 consecutive days following WHO-PAHO recommendations. Clinical and safety data were gathered from clinical files. Results: Demographic characteristics were similar between the study groups, but the size and number of lesions were higher in the MA group. Efficacy was 76.0% in the MA vs. 68.4% in the SS group (p=0.340) and 55.1% vs. 50.8% (p=0.570) in the per protocol and intention to treat analysis. respectively. Side effects more frequently reported were dysgeusia (37.0%). dizziness (32.0%). headache (36.0%). arthralgia (31.0%) and lymphangitis (21.0%). These first three symptoms as well as elevation of transaminases, leukopenia, thrombocytopenia and prolonged QTc were numerically more frequent in the SS group but without reaching statistical significance.Treatment was stopped definitively for severe toxicity in the SS group due to refractory emesis (two patients) and prolonged QTc (one patient). Conclusions: The efficacy of MA and SS is comparable. The intravenous administration of these compounds did not produce immediate reactions, but it was associated with unusualclinical and laboratory abnormalities.